Carbon Monoxide-Loaded Red Blood Cell Prevents the Onset of Cisplatin-Induced Acute Kidney Injury - Taisei Nagasaki; Hitoshi Maeda; Hiroki Yanagisawa; Kento Nishida; Kazuki Kobayashi; Naoki Wada; Isamu Noguchi; Ryotaro Iwakiri; Kazuaki Taguchi; Hiromi Sakai; Junji Saruwatari; Hiroshi Watanabe; et al. (MDPI AG, 2023)
Cisplatin-induced acute kidney injury (AKI) is an important factor that limits the clinical use of this drug for the treatment of malignancies. Oxidative stress and inflammation are considered to be the main causes of not only cisplatin-induced death of cancer cells but also cisplatin-induced AKI. Therefore, developing agents that exert antioxidant and anti-inflammatory effects without weakening the anti-tumor effects of cisplatin is highly desirable. Carbon monoxide (CO) has recently attracted interest due to its antioxidant, anti-inflammatory, and anti-tumor properties. Herein, we report that CO-loaded red blood cell (CO-RBC) exerts renoprotective effects on cisplatin-induced AKI. Cisplatin treatment was found to reduce cell viability in proximal tubular cells via oxidative stress and inflammation. Cisplatin-induced cytotoxicity, however, was suppressed by the CO-RBC treatment. The intraperitoneal administration of cisplatin caused an elevation in the blood urea nitrogen and serum creatinine levels. The administration of CO-RBC significantly suppressed these elevations. Furthermore, the administration of CO-RBC also reduced the deterioration of renal histology and tubular cell injury through its antioxidant and anti-inflammatory effects in cisplatin-induced AKI mice. Thus, our data suggest that CO-RBC has the potential to substantially prevent the onset of cisplatin-induced AKI, which, in turn, may improve the usefulness of cisplatin-based chemotherapy.